Canada, Newfoundland, and Term 29:: The Failure of Intergovernmentalism - Blake, Raymond (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
This article challenges the notion that the dispute over Term 29 resulted from the enmity between Smallwood and Diefenbaker and considers it within the history of intergovernmental relations. The two sides held contrasting views on how to address Newfoundland’s fiscal position and, without a strong federal minister from the province, Diefenbaker relied on advice of senior officials in the Department of Finance. Inevitably, the issue erupted into a bitter feud. Smallwood followed a long- established practice and attacked Ottawa vehemently, demonstrating that provincial governments are aggressive actors and have particular historical narratives to tell in the pursuit of their interests.